The Dynamics Of Indian Society Around The Event Of Partition 1947: A Take On Home As Sketched In Rahi Masoom Reza’s Aadha Gaon (Journal of Pharmaceutical Negative Results, 2022)
Aadha Gaon published in 1966 is widely known as Rahi Masoom Reza’s magnum-opus. Reza’s absolutely intricate narrationcaptures the essence of Indian society and how the social praxis changed post India’s Partition in 1947. Reza unveils that communalharmony was an element of Indian society even when at the surface level certain political parties were advocating the formation ofPakistan. The society co-existed and though there were minor disagreements among people, there was resilience and acceptance foreach other regardless of religious differences. This paper broadly studies the dynamics of the Indian society represented by Reza andalso grapples with the idea of ‘Home’ proposed by him in his works. Is home just a physical entity or is there more to it? How doesthe collective feeling of the co-existing society add up to his idea of ‘Home.’